Evaluating the seriousness of disasters: an empirical study of preferences. (15th May 2009) - Hassel, Henrik; Tehler, Henrik; Abrahamsson, Marcus
In making societal decisions concerning hazards with potentially disastrous consequences, it is important to have sound knowledge of how people evaluate the seriousness of disasters. In this study, a group of students evaluated the seriousness of disasters in terms of four basic attributes (and their ranges): number of fatalities (0-1000), number of serious injuries (0-4000), economic loss (SEK 0-40 billion) and cause of the disaster (natural, accidental, terrorism). Attribute weights were elicited by two separate methods, which taken together provide insight into the uncertainty of the elicited weights. Most participants regarded the attributes related to physical harm (especially the number of fatalities) as most serious, a finding that must be seen in relation to the ranges of the attributes. In addition, the cause of a disaster also affected many of the participants' judgements of its seriousness. This paper's findings are of value to societal decision making, particularly in the case of small to medium-sized projects in which specific elicitations of stakeholders' values are rarely made.